International Conferences Interfaces and Human Computer Interaction 2019; Game and Entertainment Technologies 2019; And Compute 2019
DOI: 10.33965/g2019_201906c055
|View full text |Cite
|
Sign up to set email alerts
|

Study of Development of Creativity Through Digital Games

Abstract: The interest in creativity has grown steadily in the last decades. Amidst this surging interest is the question of whether it is possible to aid the development of creativity. This study investigates the possibility of developing a digital game with just such objective. Therefore the game Luovus was created, utilizing previous research on the subject of creativity and digital games as learning aids. The game has been tested with a group of users and seems to be an effect on the player's self perceived creative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…Similarly, Behnamnia et al (2020) stated that digital game-based learning applications significantly affect children's creative thinking. Marin and Notargiacomo (2023) observed that digital game development through the Luovus game impacts the player's creativity. Earp et al (2013) stated that students' designing and developing games instead of playing digital games develops creativity and many skills.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Behnamnia et al (2020) stated that digital game-based learning applications significantly affect children's creative thinking. Marin and Notargiacomo (2023) observed that digital game development through the Luovus game impacts the player's creativity. Earp et al (2013) stated that students' designing and developing games instead of playing digital games develops creativity and many skills.…”
Section: Introductionmentioning
confidence: 99%